The principle of contributive capacity in relation to the health emergency COVID-19 in Ecuador, 2019 - 2020 - Orellana Ulloa, Milca Naara (2021)
Objective: Analyze the principle of contributory capacity in relation to the health emergency COVID-19. Method: The research was focused on the documentary, exploratory and descriptive study. The information was selected from the critical reading of documents and bibliographic materials, as well as official information and statistical data from national and international organizations. Results: The health emergency caused by COVID-19 has had consequences not only on people’s health, but also at social and economic levels; therefore, governments are applying various policies to overcome the crisis they are facing. In Ecuador, in the first four months of 2020 tax collection was lower by 534 million dollars compared to 2019, amount that meant a great challenge for the State as it had to generate resources to cover up for the public expenses demanded by society. Conclusion: The tax system must be configured in such a way that those with the greatest economic capacity to pay contribute to a greater extent in sustaining public charges through the prioritization of direct and progressive taxes.